Klebsiella pneumoniae Endophthalmitis with Subretinal Abscess: A Case Series and Review of the Literature - Montrisuksirikun C. (2023)
This study assessed prognostic factors and the role of vitrectomy in patients with subretinal abscesses secondary to K. pneumoniae endophthalmitis. We reviewed published studies, including three cases from our cohort. Among 50 eyes, 26 had poor visual outcomes (final visual acuity <20/800, eyeball removal, or phthisis bulbi). Poor outcomes correlated with delayed ocular symptom-to-diagnosis time, initial visual acuity <20/800, severe vitritis, and macular involvement of abscesses (p < 0.001, p = 0.008, p < 0.001, and p = 0.033, respectively). Vitrectomy had a trend towards reducing eyeball removal and phthisis bulbi rates compared with non-vitrectomy (10.8% vs 30.8%, p = 0.181). However, the final visual acuity was not different and the rate of retinal detachment tended to be higher in vitrectomized eyes (45.9% vs 15.4%, p = 0.095). The study suggested that vitrectomy and drainage of K. pneumoniae subretinal abscesses could be avoided in patients with a mild degree of vitritis.